Odpowiedzi

  • Ista
  • Rozwiązujący
2010-03-19T19:04:02+01:00
A) b+a+r+b+a+p+a+p+a = 2b+4a+r+2p
b) b-a-r-b-a-p-a-p-a = -4a-r-2p
c) a+2b+3c-4c-5b-6a = -5a-3b-c
d) a3+2a-a2+3a2-10a3+5 = -9a3+2a+2a2+5
e) 5x2-x2+y2+y-3-y+(-2)y2+5 = 4x2-y2+2
f) 13x+7y-10x-4y+5y = 3x+8y
g) 90x+3y-x2-9* 9x- 2y+x2 = 9x+y
1 5 1
2010-03-19T19:07:26+01:00
A) b+a+r+b+a+p+a+p+a
4a+2b+r+ 2p

b) b-a-r-b-a-p-a-p-a
-4a-r-2p

c) a+2b+3c-4c-5b-6a
-5a-3b-c

f) 13x+7y-10x-4y+5y
3x8y

g) 90x+3y-x2-9* 9x- 2y+x2
90x + 3y-x2 - 81x - 2 +x2
11x+ 3y-2

Tyle potrafie :)
1 5 1